Co-Founder - Mouzouropoulos, Theseas (My University, 2026)
A two-day event consisting of lectures, workshops, discussions by designers & artists. The platform expands its spectrum beyond conventional visual communication and furthermore explores the opposed landscapes of both artistic and digital expression. Proudly announcing the 1st Prototype Conference, a two-day event that consists of a series of lectures, workshops, panel discussions by international and local designers and artists with distinguished and awarded work. The lectures, panels discussion and networking will take place, on Saturday, 9th December from 5:00 to 8:00 PM at Amphitheater 1, Tassos Papadopoulos Building of TEPAK (corner of Themidos and Iphigenia in Limassol). The official guest speakers for this 1st Prototype Conference are Europium Creative and Art Direction studio (France), Pantelis Diamantides (Cyprus), Omiros Panayides (Cyprus) and Lefki Savvidou (Cyprus). Additionally, on the following day, Sunday 10th December from 10:00 am–3.00pm Pantelis Diamantides and Lefki Savvidou will conduct two separate workshops at the Art and Design Workshop (ETS) and Graphic Design Lab, Heroes Square, Limassol. Prototype expands its spectrum beyond conventional visual communication and will explore the opposed landscapes of both artistic and digital expression. The Prototype Conference aims to capture the essence of its name by embracing the spirit of innovation, exploration, and dialogue in its creative aspirations. The platform welcomes diverse technologies and innovative use of media, in both creation and dissemination, while also reflecting our enduring interest in traditional media and artistic forms. The event is organised by the research labs SVC lab (Semiotics & Visual Communication Research Lab), LGCRL (Language & Graphic Communication Research Lab) of the Department of Multimedia and Graphic Arts of Cyprus University of Technology and TYPOMEDIA LAB of Frederick University.